The Maximal Pore Size of Hydrophobic Microporous Membranes Does Not Fully Characterize the Resistance to Plasma Breakthrough of Membrane Devices for Extracorporeal Blood Oxygenation - Fragomeni, Gionata; Terzini, Mara; Comite, Antonio; Catapano, Gerardo (Frontiers in Bioengineering and Biotechnology, 2020)
hydrophobic membranes has become routine treatment of respiratory or cardiac failure. In spite of membrane hydrophobicity, significant amounts of plasma water may form in the gas compartment during treatment, an event termed plasma water breakthrough. When this occurs, plasma water occludes some gas pathways and ultimately cripples the oxygenator gas exchange capacity requiring its substitution. This causes patient hemodilution and increases the activation of the patient’s immune system. On these grounds, the resistance to plasma water breakthrough is regarded as an important feature of ECMO devices. Many possible events may explain the occurrence of plasma breakthrough. In spite of this, the resistance to plasma breakthrough of ECMO devices is commercially characterized only with respect to the membrane maximal pore size, evaluated by the bubble pressure method or by SEM analysis of membrane surfaces. The discrepancy between the complexity of the events causing plasma breakthrough in ECMO devices (hence determining their resistance to plasma breakthrough), and that claimed commercially has caused legal suits on the occasion of the purchase of large stocks of ECMO devices by large hospitals or regional institutions. The main aim of this study was to identify some factors that contribute to determining the resistance to plasma breakthrough of ECMO devices, as a means to minimize litigations triggered by an improper definition of the requirements of a clinically efficient ECMO device. The results obtained show that: membrane resistance to breakthrough should be related to the size of the pores inside the membrane wall rather than at its surface; membranes with similar nominal maximal pore size may exhibit pores with significantly different size distribution; membrane pore size distribution rather than the maximal pore size determines membrane resistance to breakthrough; the presence of surfactants in the patient’s blood (e.g. lipids, alcohol, etc.) may significantly modify the intrinsic membrane resistance to breakthrough, more so the higher the surfactant concentration. We conclude that the requirements of ECMO devices in terms of resistance to plasma breakthrough ought to account for all these factors and not rely only on membrane maximal pore size.